Root morphology and biomechanical characteristics of high altitude alpine plant species and their potential application in soil stabilization - Hudek, C.; Sturrock, Craig; Atkinson, B.S.; Stanchi, S.; Freppaz, M. (Elsevier, 2017)
Glacial forefields host young, poorly developed soils with highly unstable environmental conditions. Root system contribution to soil stabilization is a well-known phenomenon. Identifying the functional traits and root morphology of pioneer vegetation that establish on forefields can provide information useful in the practical application of plants in land restoration of high altitude mountain sites.This study aims to gather information on the root morphology and biomechanical characteristics of the 10 most dominant pioneer plant species of the forefield of Lys Glacier (NW Italian Alps).X-ray Computed Tomography (X-ray CT) was used to visualize and quantify non-destructively the root architecture of the studied species. Samples were cored directly from the forefield. Data on root traits such as total root length, rooting depth, root diameter, root length density and number of roots in relation to diameter classes as well as plant height were determined and compared between species. Roots were also tested for their tensile strength resistance.X-ray CT technology allowed us to visualize the 3D root architecture of species intact in their natural soil system. X-ray CT technology provided a visual representation of root-soil interface and information on the exact position, orientation and elongation of the root system in the soil core. Root architecture showed high variability among the studied species. For all species the majority of roots consisted of roots smaller than 0.5. mm in diameter. There were also considerable differences found in root diameter and total root length although these were not statistically significant. However, significant differences were found in rooting depth, root length density, plant height and root tensile strength between species and life forms (dwarf shrub, forb, graminoid). In all cases, root tensile strength decreased with increasing root diameter. The highest tensile strength was recorded for graminoids such as Luzula spicata (L.) DC. and Poa laxa Haenke and the lowest for Epilobium fleischeri Hochst.The differences in root properties among the studied species highlight the diverse adaptive and survival strategies plants employ to establish on and thrive in the harsh and unstable soil conditions of a glacier forefield. The data determined in this study could provide a significant contribution to a database that allow those who are working in land restoration and preservation of high altitude mountain sites to employ native species in a more efficient, effective and informed manner.